2016
DOI: 10.1021/acs.chemrestox.6b00181
|View full text |Cite
|
Sign up to set email alerts
|

Activating Transcription Factor 4 (ATF4)-ATF3-C/EBP Homologous Protein (CHOP) Cascade Shows an Essential Role in the ER Stress-Induced Sensitization of Tetrachlorobenzoquinone-Challenged PC12 Cells to ROS-Mediated Apoptosis via Death Receptor 5 (DR5) Signaling

Abstract: Tetrachlorobenzoquinone (TCBQ) is a downstream metabolite of pentachlorophenol (PCP). Previously, we demonstrated that TCBQ caused cytotoxicity due to mitochondrial-related apoptosis. Here, we confirmed the upregulation of death receptor 5 (DR5) followed by the construction of the death-inducing signaling complex (DISC). We also detected the activation of the caspase cascade, which was correlated with TCBQ-induced apoptotic cell death in PC12 cells. The upregulation of DR5 included transcriptional activation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 33 publications
(51 reference statements)
6
34
0
Order By: Relevance
“…With the highest score, an unidentified gene FP236383.10 with a prediction of being a miRNA in the databases, decreased the most, which remains for further investigation. All other genes were remarkably up-regulated for their transcription, among which the proteins of osgin1 [31], [32], hmox1 [33], [34], atf3 [35], [36], spns2 [37], ppp1r15a [38] and tiparp [39] possess certain degree of relationship with redox homeostasis, suggesting that the change of RPL10 is closely associated with redox homeostasis in the cells. To verify such a relationship, two typical proteins involved in redox homeostasis, OSGIN1 and HMOX1, were chosen for experimental verification.…”
Section: Resultsmentioning
confidence: 99%
“…With the highest score, an unidentified gene FP236383.10 with a prediction of being a miRNA in the databases, decreased the most, which remains for further investigation. All other genes were remarkably up-regulated for their transcription, among which the proteins of osgin1 [31], [32], hmox1 [33], [34], atf3 [35], [36], spns2 [37], ppp1r15a [38] and tiparp [39] possess certain degree of relationship with redox homeostasis, suggesting that the change of RPL10 is closely associated with redox homeostasis in the cells. To verify such a relationship, two typical proteins involved in redox homeostasis, OSGIN1 and HMOX1, were chosen for experimental verification.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated that ER stress increases the transcription of the gene encoding DR5 through activation of transcription factors ATF4 and CHOP (Chen, Hu et al, 2016, Liu, Shi et al, 2016. Therefore, we examined whether tcyDTDO activates a previously described (Cheong et al, 2011) DR5 transcriptional reporter construct.…”
Section: Ddas Upregulate Dr5 Through Both Transcriptional and Posttramentioning
confidence: 96%
“…ATF3 and ATF4 belong to the ATF/cAMP response element binding (ATF/CREB) family of transcription factors. 21,62 Members of the ATF/CREB family sense environmental stimulation signals and participate in cellular processes. Liu reported that the UPR increases ATF3 expression via p-eIF2-ATF4 signaling.…”
Section: Dovepressmentioning
confidence: 99%
“…It was previously reported that ATF3 played an integral part in the PERK/eIF2 signaling branch of the UPR. 21 PERK/ eIF2 cascade has been proved to be a remarkable pathway that could influence apoptosis. 22 For the past few years, multiple researchers have reported a potential correlation in ATF4/ATF3/CHOP.…”
Section: Introductionmentioning
confidence: 99%